Sap Beetles (of Florida), Nitidulidae (Insecta: Coleoptera: Nitidulidae) - Lisa Myers (EDIS)
Most species of sap beetles are attracted to the wounds of trees where they feed on sap. However, the habits of the Nitidulidae are quite variable (Parsons 1943). Sap beetles have been found in various habitats feeding on flowers, fruits, sap, fungi, decaying and fermenting plant tissues or dead animal tissue (Parsons 1943, Hayashi 1978). This document is EENY-256, one of a series of Featured Creatures from the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: November 2001. Revised: September 2004.